Reduced Modeling of Unbalanced Radial Distribution Grids in Load Area Framework - Giovanni Mercurio Casolino; Arturo Losi (IEEE Access, 2020)
A simplified representation of a distribution network offers relevant advantages in limiting the amount of information processed and reducing the computational burden necessary for its treatment, in particular in planning studies, real-time simulations, monitoring and control. The identification of the relevant information for obtaining a correct reduced modeling of a distribution network results from the Load Area (LA) approach. It is based on the concept of groups of nodes/prosumers whose power injection has a similar impact on the operating conditions of distribution grids; the groups are identified through overload and voltage indexes. The paper presents a method for obtaining the reduced equivalent modeling of unbalanced radial grids in the LA framework, once the LAs have been identified. It is based on the backward-forward graph navigation technique for radial grids and a generalization of the modeling of single-phase and two-phase branches. The application and discussion of the method for five different size test cases highlight the computational issues related to the representation and solution of the reduced networks. The results show the feasibility of the proposed method and highlight the computational gains deriving from its adoption.